Social Media in Pediatric Orthopaedics. Issue 7 (October 2017) - Lander, Sarah T.; Sanders, James O.; Cook, Peter C.; O'Malley, Natasha T.
Abstract : Background: Internet searches and social media utilization in health care has exploded over the past 5 years, and patients utilize it to gain information on their health conditions and physicians. Social media has the potential to serve as a means for education, communication, and marketing in all health care specialties. Physicians are sometimes reluctant to engage because of concerns of privacy, litigation, and lack of experience with this modality. Many surgical subspecialties have capitalized on social media but no study to date has examined the specific footprint of pediatric orthopaedic surgeons in this realm. We aim to quantify the utilization of individual social media platforms by pediatric orthopaedic surgeons, and identify any differences between private and hospital-based physicians, but also regional differences. Methods: Using the Pediatric Orthopaedic Society of North America Member Directory, each active member's social media presence was reviewed through an Internet search. Members were stratified on the basis of practice model and geographic location. Individual Internet searches, social media sites, and number of publications were reviewed for social media presence. Results: Of 987 Pediatric Orthopaedic Society of North America members, 95% had a professional webpage, 14.8% a professional Facebook page, 2.2% a professional Twitter page, 36.8% a LinkedIn profile, 25.8% a ResearchGate profile, 33% at least 1 YouTube. Hospital-based physicians had a lower mean level of utilization of social media compared with their private practice peers, and a higher incidence of Pubmed publications. Private practice physicians had double the social media utilization. Regional differences reveal that practicing Pediatric Orthopaedists in the Northeast had increased utilization of ResearchGate and LinkedIn and the West had the lowest mean social media utilization levels. Conclusions: The rapid expansion of social media usage by patients and their family members is an undeniable force affecting the health care industry. The Internet and social media platforms provide all physicians with a means to educate patients, collaborate with colleagues, and promote their practice and areas of interest. Our survey indicates that pediatric orthopaedic surgeons may be underutilizing their potential social media presence. Levels of Evidence: Level IV.